2021
DOI: 10.3390/plants10091968
|View full text |Cite
|
Sign up to set email alerts
|

Bordered Pit Formation in Cell Walls of Spruce Tracheids

Abstract: The process of pit formation in plants still has various questions unaddressed and unknown, which opens up many interesting and new research opportunities. The aim of this work was elucidation of the mechanism for the formation of bordered pits of the spruce (Picea abies (L.) Karst.) tracheid with exosomes participation and mechanical deformation of the cell wall. Sample sections were prepared from spruce stem samples after cryomechanical destruction with liquid nitrogen. The study methods included scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…The thin parts that form at certain points were called pits. The protoplasmic filaments that connected two adjacent cells to each other through the stria were called plasmodesmata, which were the bridge between cells for direct material and information contact ( Sasaki et al., 2017 ; Chukhchin et al., 2021 ). In order to further investigated the changes in pits during lignification of stone cells and the effect of pits on the initiation of lignin processes in parenchymal cells, we carried out ultramicroscopic observations of the changes in pits in stone cells of DY and DW ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thin parts that form at certain points were called pits. The protoplasmic filaments that connected two adjacent cells to each other through the stria were called plasmodesmata, which were the bridge between cells for direct material and information contact ( Sasaki et al., 2017 ; Chukhchin et al., 2021 ). In order to further investigated the changes in pits during lignification of stone cells and the effect of pits on the initiation of lignin processes in parenchymal cells, we carried out ultramicroscopic observations of the changes in pits in stone cells of DY and DW ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Stone cells develop through secondary thickening of the cell wall and lignin deposition. Uneven thickening of the secondary wall causes single pit to start to form( Lian et al., 2020 ; Chukhchin et al., 2021 ). Lignin deposition similar to numerous discrete granules first occur at the corner of the middle lamella (ML) within various primary cell walls.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental data has demonstrated that EVs extracted from the leaf apoplast encapsulate miRNAs, secondary small interfering RNAs (siRNAs), and a class of “tiny RNAs,” in addition to protein–RNA complexes localized to the outer EV membrane ( Cai et al 2018 , 2021 ; Baldrich et al 2019 ; Cai et al 2019 ; Zand Karimi et al 2022 ). Although the prospect of EVs in the apoplast driving the movement of RNAs and proteins is exciting, only one group has documented the presence of EVs in plant vasculature ( Chukhchin et al 2020 , 2021 ). Using atomic force microscope imaging, this group has demonstrated the presence of exosomes in axial phloem and xylem parenchyma; however, the function of these EVs remains unconfirmed ( Chukhchin et al 2020 ; van Bel 2021 ).…”
Section: Molecular Superhighway: Mrna Transit Through the Phloemmentioning
confidence: 99%
“…This soft matrix layer is fused, dissolved, or removed during enzymatic treatment, making the pits porously open. In the study of border pits formation in cell walls of spruce tracheid, when the wood is treated with pectinase enzyme, the torus is hydrolyzed, and the matrix of micro-fibrils is visible, meanwhile, when the wood is treated with xylanase enzyme, the torus, margo, and border are visibly unchanged [8]. In this case, the pectinase enzyme is more suitable for treating spruce tracheid as it is compared with xylanase.…”
Section: Introductionmentioning
confidence: 99%